Redundant Words as an Index of Oral Communication Ability: An Application of Pragmatics to Language Teaching - Pen-Ying Wang (National Taipei University of Education, 2022)
The present study proposes that redundant words often found in college students' presentations can serve as an index of oral communication ability. By analyzing the data collected from a Chinese Phonetics and Oral Communication course, the redundancies were found to not only carry pragmatic functions but also reflect the cognition of the speakers. ‟Jiushi" serves as a pragmatic function to emphasize and to conclude, and ‟ranhou" bears the pragmatic function of pause fillers. The results show a mild correlation between the frequency of redundant words used and students' oral performance. The more ‟jiushi" were found in the students' production, the lower their grades were given by their peers. Similarly, the more ‟ranhou" used in students' presentations, the less confident the students were in presenting the content. As instructors are aware of the real cause of using redundant words, ‟cutting down redundancies" would be the last suggestion a teacher would offer the students.